Świadectwo obrazu. Związki ekfrazy i pamięci w Zobaczonym Julii Hartwig - Telicki, Marcin (Wydawnictwo Naukowe UAM, 2009)
In the article The evidence of the image..., the author reflects on two important problems in modern culture: considers the role of ekphrasis - the introduction of which connotes the concepts of iconicity, vividness and representation; and memory processes derived from descriptions of pieces of painting (but also views of nature). It appears that the change in time, that introduces changes to the perception, is shared by the two phenomena. Theoretical considerations are developed and legitimised by interpretations of poems from the volume Zobaczone. In her poetry, Julia Hartwig, sometimes considered as one of the Old Masters of poetry, very consistently combines interest in the visuality of the world and problems of recording continuity. Hence, it is advisable to analyse her poems as a play between the elusive image and its material evidence.
The evidence of the image. The relationships of ekphrasis to memory in Julia Hartwig's Zobaczone (What's been seen)